1994
DOI: 10.1080/02827589409382810
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term effects of temperature on the wood production of Pinus sylvestris L. and Picea abies (L.) Karst. In old provenance experiments

Abstract: Old provenance experiments with Scots pine and Norway spruce in Finland were used for assessing the long-term effects of the projected climatic change on forest trees. The northernmost origins showed an increase in wood production when transferred southwards into a climate with an annual mean effective temperature sum close to that which is expected in northern areas as a result of the projected climatic change. A model is constructed with the estimated changes in wood production as a function of the annual me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
0
1

Year Published

1997
1997
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(40 citation statements)
references
References 14 publications
3
36
0
1
Order By: Relevance
“…A more pronounced effect of T at low current temperature sum was to be expected (III), because low summer temperature limits growth more in northern than in southern Finland (Mäkinen et al 2002). Similarly, in provenance experiments trees of northern origin have been found to benefit more from increasing temperatures (Beuker 1994). Also in this work (III), the simulations' results were in line with the assumptions regarding Scots pine and silver birch, which reacted to elevated T more vigorously at sites with a low current temperature sum.…”
Section: Performance Of the Transfer Functionssupporting
confidence: 75%
“…A more pronounced effect of T at low current temperature sum was to be expected (III), because low summer temperature limits growth more in northern than in southern Finland (Mäkinen et al 2002). Similarly, in provenance experiments trees of northern origin have been found to benefit more from increasing temperatures (Beuker 1994). Also in this work (III), the simulations' results were in line with the assumptions regarding Scots pine and silver birch, which reacted to elevated T more vigorously at sites with a low current temperature sum.…”
Section: Performance Of the Transfer Functionssupporting
confidence: 75%
“…In Beuker's (1994) data, growth increased relative to the natural rate of growth, when trees were taken from northern Finland and transplanted to southern Finland into an environment 2-5 centigrade warmer than the site from which the seed was collected. He concluded that in areas where low temperature is the major limiting factor for increment, tree growth would benefit from an increase in annual mean temperature.…”
Section: The Eventual Carbon Feedbackmentioning
confidence: 99%
“…He concluded that in areas where low temperature is the major limiting factor for increment, tree growth would benefit from an increase in annual mean temperature. Beuker (1994) refers mainly to the responses of trees in the northern parts of Finland (see also Karjalainen 1996a,b).…”
Section: The Eventual Carbon Feedbackmentioning
confidence: 99%
“…The impact will be seen primarily as an increase in growth and productivity resulting from the prolonged growing season (Junttila and Nilssen, 1993;Beuker, 1994;Fries et al, 1998). At the timberline ecotone, the growing season is expected to change from the present 110 -120 days up to 150 -160 days by 2100 (Kellomäki et al, 1997).…”
Section: Introductionmentioning
confidence: 99%